Tuberculosis and genes of the IL12/IL23/IFNγ pathway: Exploring functional significance of novel mutations in the IL12p40 promoter - Pienaar, Sandra Margaret (Department of Paediatrics and Child Health, 2014)
Includes bibliographical references.